Volatile‐mediated tritrophic defense and priming in neighboring maize against Ostrinia furnacalis and Mythimna separata. Issue 1 (30th September 2022) - Foba, Caroline Ngichop; Shi, Jin‐Hua; An, Qing‐Qing; Liu, Le; Hu, Xin‐Jun; Hegab, Mahmoud Ali Morse Soliman; Liu, Hao; Zhao, Pei‐Min; Wang, Man‐Qun
Abstract: Background: Plants respond to attackers by triggering phytohormones signaling associated metabolites, including herbivore‐induced plant volatiles (HIPVs). HIPVs can indirectly act against herbivory by recruitment of natural enemies and priming of neighboring plants. Ostrinia furnacalis and Mythimna separata are important insect herbivores of maize plants that have a devastating influence on yield. However, little is known about how maize temporally reconfigures its defense systems against these herbivores and variation of neighboring plant resistance. Results: This study investigated the effects of HIPVs on the behavior of the dominant predatory beetle Harmonia axyridis and priming in neighboring maize defense against O. furnacali s and M. separata over time. The results showed that maize damaged by either O. furnacalis or M. separata enhanced the release of volatiles including terpenes, aldehydes, alkanes and an ester, which elicited an increased attractive response to H. axyridis after 3 and 12 h, respectively. O. furnacalis damage resulted in accumulations of leaf jasmonic acid (JA) and salicylic acid in maize after 6 and 3 h, respectively, while M. separata damage only raised the JA level after 3 h. Furthermore, HIPVs were able to prime neighboring plants through the accumulation of JA after 24 h. Both larvae showed a significant decrease in weight accumulation after 48 h of feeding on the third leaves of the primed plant. Conclusion: Taken together, the findings provide a dynamic overview of how attacked maize reconfigures its volatiles and phytohormones to defend against herbivores, as well as priming of neighboring plants against oncoming attacks. © 2022 Society of Chemical Industry. Abstract : Herbivore‐induced plant volatiles (HIPVs) recruit natural enemies and prime the neighboring plants. They accumulate jasmonic acid content in neighboring plants and enhance the neighboring plants defense ability to larval feeding.